Oil, Macroeconomics, and Forests : Assessing the Linkages - Wunder, Sven; Sunderlin, William D. (World Bank, 2013)
This article focuses mainly on the five primary case study countries. For forest impacts, the concentration is on forest conversion to other land uses and deforestation, defined as a (temporary or permanent) removal of trees to less than 10 percent crown cover, which is similar to the Food and Agricultural Organization's (FAO's) definition. Selective logging is thus not deforestation but may degrade forests and enable conversion. All of the case study countries are tropical countries that export oil, a choice made for two reasons. First, the macroeconomic 'laboratory' of oil exporters offers a good opportunity to study links between external economic changes and forests. Oil economies often fluctuate dramatically due to heavy reliance on a single export commodity with unstable world market prices. Second, earlier studies provide support for the hypotheses that on average oil- and mineral-exporting tropical countries have more forests left and lose them at a slower rate than non-mineral-exporting countries. The article briefly reviews hypotheses and methodologies and outlines the deforestation data problems and how they were dealt with. It presents empirical results for the five primary case study countries and takes a closer look at three of the key causal linkages in the model. It then examines the role of different policy instruments and finally discusses policy insights that extend beyond the oil exporting countries.